Transformasi Perlindungan Hukum Ketenagakerjaan di Indonesia : Analisis Kesadaran Hak Pekerja dalam Perspektif Undang-Undang Cipta Kerja (Neolectura, 2026)
This study examines the transformation of labor law protection in Indonesia by focusing on the level of workers’ legal awareness regarding their rights within industrial relations. The reform of labor regulations through Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja and its subsequent reinforcement in Undang-Undang Nomor 6 Tahun 2023 tentang Penetapan Perppu Cipta Kerja has significantly altered the structure and orientation of the national labor system. This research employs a descriptive qualitative approach through a literature study, analyzing statutory regulations, academic literature, and empirical phenomena related to labor practices. The findings reveal that although regulatory reforms aim to enhance investment and economic growth, they also generate complex implications for labor protection. These include the weakening of job security, expansion of flexible work arrangements such as outsourcing, and persistent imbalance in bargaining power between workers and employers. Furthermore, the study highlights that the effectiveness of legal protection is not solely determined by the existence of regulations, but is also influenced by the level of legal awareness among workers, accessibility to legal remedies, and the consistency of law enforcement. The low level of legal literacy among workers contributes to their vulnerability in facing unfair labor practices. Therefore, the study concludes that labor law reform must be accompanied by strengthening institutional oversight, improving legal education, and fostering a legal culture that supports social justice. A balanced approach between economic development and labor protection is essential to ensure sustainable and equitable industrial relations in Indonesia.